Development of a prospective web-based inventory system for management of lab facilities - A.N., Mustafizul Karim; Saad, Mohd Fadli; Mahbubul, Haque (Scholarlink Research Institute Journals, 2011)
Inventory management is a prime task for an organization to achieve its goals of maintaining appropriate level of inventory and minimizing waste. A web-based system of managing inventory in a university setting is expected to help various laboratories keep an update on the status of their tools and equipment. In this study, a model is presented for putting a web-based inventory system in place in five different laboratories of an Engineering Department in a large public university in Malaysia. In designing such a system, PHP has been employed as a development language and MySQL as a backend database with CSS implemented for the interface. Two screen-shots have been illustrated to offer a glimpse of the proposed web-based system and its applications. This online system would help the personnel in charge of the laboratories find out the capacity of the labs as well as the relevant information of asset availability, and replace the current practice of extensive manual recording of asset documentation thus holding a key for an organization like university to gaining competitive advantage through efficient operational performance. __________________________________________________________________________________________